2023
DOI: 10.1002/hep.32640
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage‐specific FGF12 promotes liver fibrosis progression in mice

Abstract: Background and Aims: Chronic liver diseases are associated with the development of liver fibrosis. Without treatment, liver fibrosis commonly leads to cirrhosis and HCC. FGF12 is an intracrine factor belonging to the FGF superfamily, but its role in liver homeostasis is largely unknown. This study aimed to investigate the role of FGF12 in the regulation of liver fibrosis.Approach and Results: FGF12 was up-regulated in bile duct ligation (BDL)-induced and CCL 4 -induced liver fibrosis mouse models. Expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…In all three models, we observed a significant improvement in myocardial hypertrophy within one week after the AAV9-FGF12 injection, most notably in the left ventricular free wall. While these results suggest that FGF12 conferred some therapeutic effects in mice with myocardial hypertrophy, we also noted that fibrosis was exacerbated after myocardial hypertrophy in mice treated with FGF12 (Supplemental 2A-D), consistent with the findings of previous studies in liver fibrosis 21 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In all three models, we observed a significant improvement in myocardial hypertrophy within one week after the AAV9-FGF12 injection, most notably in the left ventricular free wall. While these results suggest that FGF12 conferred some therapeutic effects in mice with myocardial hypertrophy, we also noted that fibrosis was exacerbated after myocardial hypertrophy in mice treated with FGF12 (Supplemental 2A-D), consistent with the findings of previous studies in liver fibrosis 21 .…”
Section: Discussionsupporting
confidence: 91%
“…Under normal physiological conditions, GATA4 is distributed in both perinuclear and intranuclear regions. However, during myocardial hypertrophy, GATA4 undergoes phosphorylation and strictly localizes in the nucleus [21][22][23] . Our results indicate that GATA4 co-localizes with FGF12 in perinuclear regions under physiological conditions and shifts to the nucleus in hypertrophic cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bhatia et al revealed that Ly6C hi promotes kidney fibrosis in mice via the PINK1/MFN2/Parkin-mediated pathway . Li et al reported that suppressing the infiltration of Ly6C hi monocytes can alleviate liver fibrosis . Combined with these, inhibiting Ly6C hi macrophage phenotypic transformation or increasing the Ly6C lo number may be a promising approach for treating liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…29 Li et al reported that suppressing the infiltration of Ly6C hi monocytes can alleviate liver fibrosis. 30 Combined with these, inhibiting Ly6C hi macrophage phenotypic transformation or increasing the Ly6C lo number may be a promising approach for treating liver fibrosis. Herein, it was found that Sch B could upregulate the number of Ly6C lo .…”
Section: ■ Discussionmentioning
confidence: 99%
“…further reported that c-mer tyrosine kinase (MerTK) signaling in macrophages activates HSCs to promote collagen synthesis and induces liver fibrosis through the ERK-TGFβ1 pathway ( 40 ). In bile duct ligation (BDL)-induced and carbon tetrachloride (CCl4)-induced liver fibrosis mouse models, the FGF12-mediated proinflammatory activation of hepatic macrophages could induce HSC activation mainly through the monocyte chemoattractant protein-1/chemokine (C-C motif) receptor 2 axis ( 42 ). The roles of MoMϕs in liver fibrosis were also investigated.…”
Section: Liver Fibrosis and Macrophagesmentioning
confidence: 99%